Traffic Accident Analysis Model In Traffic Accidents That Have No Witness - Riyanto Yunus (Universitas Negeri Gorontalo, 2022)
The problem of traffic accidents in the absence of witnesses is very crucial because in traffic accidents, in principle, the presence of witnesses is very important in determining the suspect and victim. Therefore, it is important to reconstruct traffic accident analysis (TAA) in every traffic accident. This is the concern of the compilers to examine how the concept of implementing Traffic Accident Analysis in traffic accidents, as well as to examine the Traffic Accident Analysis proof model in traffic accidents that do not have witnesses. The type of research in writing this proposal is normative research, which includes research on legal systematics, research on the level of legal synchronization, research on legal history, and research on comparative law. The results show that the concept of applying Traffic Accident Analysis in traffic accidents uses two main methods, namely: clinical and statistical approaches. The application of Traffic Accident Analysis is very important to do and becomes an alternative when there is no witness in a traffic accident. This is necessary to assist investigators in reconstructing accidents and determining suspects and victims